2020
DOI: 10.1002/sctm.20-0378
|View full text |Cite
|
Sign up to set email alerts
|

A replicating stem-like cell that contributes to bone morphogenetic protein 2-induced heterotopic bone formation

Abstract: Bone morphogenetic protein 2 (BMP2)-induced heterotopic bone formation (HBF) starts synchronously from zero upon BMP2 induction, which is advantageous for lineage tracking. The studies reported here in GLAST-Cre Ert2 :tdTomato red (TR) floxSTOPflox mice during BMP2-induced HBF show 78.8 ± 11.6% of chondrocytes and 86.5 ± 1.9% of osteoblasts are TR + after approximately 1 week. Clustering after single-cell RNAseq resulted in nine cell types, and analysis revealed one as a highly replicating stem-like cell (RSC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…The earliest cell type in the genesis of ADRβ3+ macrophages is MH6, which appears to undergo further changes to form other M2 macrophages ( Supplemental Figure 4C ). It is interesting that MH6 shows high homology to the Replicating Stem-like Cell, which is a stem-like cell for osteogenesis that goes next to the Chondro-Osseous Progenitor (COP) through an epithelial to mesenchymal transition ( 44 ). The MH6 progenitor leads directly to MH7 ( Supplemental Figure 4 ), that contains markers of hemogenic endothelial cells and MH7 is the progenitor for MH0.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest cell type in the genesis of ADRβ3+ macrophages is MH6, which appears to undergo further changes to form other M2 macrophages ( Supplemental Figure 4C ). It is interesting that MH6 shows high homology to the Replicating Stem-like Cell, which is a stem-like cell for osteogenesis that goes next to the Chondro-Osseous Progenitor (COP) through an epithelial to mesenchymal transition ( 44 ). The MH6 progenitor leads directly to MH7 ( Supplemental Figure 4 ), that contains markers of hemogenic endothelial cells and MH7 is the progenitor for MH0.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 To confirm these findings, researchers led by Alan R. Davis (Baylor College of Medicine, Houston, Texas) employed a mouse reporter model (GLAST-Tomato Red) to identify the exact progenitor population responsible for BMP2-induced heterotopic bone formation. As reported in their STEM CELLS Translational Medicine article, 11 Mejia et al employed highly sensitive single-cell RNA sequencing of fluorescently labeled chondrocytes and osteoblasts after BMP2-induced heterotopic bone formation and identified a highly replicating stem-like cell or RSC as a candidate for study. The authors demonstrated that RSCs undergo an epithelial-to-mesenchymal transition (like neural crest stem cells) to produce mesenchymal stem cell-like cells that express osteoblast and chondrocyte transcripts and generate bone and cartilage tissue.…”
Section: Bmp2-induced Heterotopic Bone Formation By Newly Identified Highly Replicating Stem Cellsmentioning
confidence: 99%
“…Further insight into BMP‐mediated signaling may aid the efficient differentiation of stem/progenitor cells into therapeutically relevant somatic cell types and further our understanding of diverse human pathologies associated with aberrant BMP pathway regulation 10 . In the second of our Featured Articles published this month in STEM CELLS Translational Medicine , Mejia et al identify a highly replicating stem‐like cell (RSC) as the early stem/progenitor cell that initiates BMP2‐induced heterotopic bone formation 11 . In a Related Article published recently in STEM CELLS , Dries et al systematically profiled multiple components of the TGFβ signaling pathway during neural differentiation to reveal the existence of cell‐stage specific networks of individual components 12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant enhanced osteogenesis within soft tissues responding to the trauma has long been discussed to be the core mechanism for the development of HO. Despite the diversity of stimulus that cause HO, it has been reported that the osteogenic signals remained greatly elevated during HO progression and committed progenitor cells to enhanced osteogenic behavior 8,9 . In the studies incorporating brain‐trauma or burn‐injury into animal models that recapitulate the trauma‐induced HO, the osteogenic activities of relevant progenitor cells can even be further reinforced by these concomitant injuries that are clinically relevant in the context of HO formation 10,11 .…”
Section: Introductionmentioning
confidence: 99%